2020
DOI: 10.3389/fevo.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Exposure to Simulated Winter Storm Cues Negatively Affect White-Throated Sparrow (Zonotrichia albicollis) Energy Reserves

Abstract: Birds are often able to cope with, and respond to, inclement weather with physiological and behavioral responses. As storms become more severe or frequent as a result of climate change, the adaptive coping responses of many species may be pushed beyond current tolerance limits. We investigated the effects of experimental recurrent inclement winter weather cues on body composition, glucocorticoid hormones, and behavior of white-throated sparrows (Zonotrichia albicollis). We used a hypobaric climatic wind tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, trapping efforts indicated that mole-rats appeared to exhibit reduced activity during periods of rain when compared to clear days. It is possible that mole-rats may be able to respond to the change in air pressure or temperature caused by the rain or cold fronts as seen in other animals (Garthe et al, 2009;Boyer and MacDougall-Shackleton, 2020). Lastly, because Natal mole-rats exhibit only behavioral reproductive suppression compared to that of the Damaraland mole-rats, which exhibit behavioral and physiological suppression (Bennett et al, 1996;Molteno and Bennett, 2000;Oosthuizen et al, 2008), we predicted that locomotor activity differences between the breeders and nonreproductive individuals would be less distinct than in species with higher reproductive skew.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, trapping efforts indicated that mole-rats appeared to exhibit reduced activity during periods of rain when compared to clear days. It is possible that mole-rats may be able to respond to the change in air pressure or temperature caused by the rain or cold fronts as seen in other animals (Garthe et al, 2009;Boyer and MacDougall-Shackleton, 2020). Lastly, because Natal mole-rats exhibit only behavioral reproductive suppression compared to that of the Damaraland mole-rats, which exhibit behavioral and physiological suppression (Bennett et al, 1996;Molteno and Bennett, 2000;Oosthuizen et al, 2008), we predicted that locomotor activity differences between the breeders and nonreproductive individuals would be less distinct than in species with higher reproductive skew.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies ( Awerman & Romero, 2010 ; Cyr et al, 2007 ; Fokidis et al, 2011 ; Kern et al, 2007 ; Xie et al, 2015 ) showed no change in plasma glucose with chronic stress. We were unable to find any other papers on changes in ketones with chronic stress in birds, but changes in fat scores suggest that fat mobilization can be affected by chronic stress ( Boyer & MacDougall-Shackleton, 2020 ). Uric acid has been reported to not change ( Xie et al, 2015 ), increase ( Gormally et al, 2019a ), or decrease ( Gormally et al, 2019b , 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…Severe storms can be life-threatening, thus it is beneficial for birds to predict the weather and adjust their behaviour to suit (Cohen et al 2021). Lower temperatures, rainfall and wind increase metabolic expenditure, which negatively affects their body condition and ability to incubate eggs (Breuner et al 2013;Boyer and MacDougall-Shackleton 2020). Inclement weather coping responses include increasing foraging activity (Metcalfe et al 2013;Boyer and MacDougall-Shackleton 2020), nest-maintenance behaviour (Laux et al 2016), migration (Boyle et al 2010), and abandonment of territories (Streby et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lower temperatures, rainfall and wind increase metabolic expenditure, which negatively affects their body condition and ability to incubate eggs (Breuner et al 2013;Boyer and MacDougall-Shackleton 2020). Inclement weather coping responses include increasing foraging activity (Metcalfe et al 2013;Boyer and MacDougall-Shackleton 2020), nest-maintenance behaviour (Laux et al 2016), migration (Boyle et al 2010), and abandonment of territories (Streby et al 2015). Many of these behaviours occur just prior to an extreme weather event, which suggests that birds can predict the coming weather and prepare for it.…”
Section: Introductionmentioning
confidence: 99%